ChM. Dr. Wan Norfazilah s LabQuest Enhancing students understanding of laboratory quality management - Nur Hartini, Mohd Hatta (UMPSA, 2024)
PEKAN, 14 October 2024 – A lecturer at the Faculty of Industrial Science and Technology (FSTI), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), ChM. Dr. Wan Norfazilah Wan Ismail, 36, has developed a board game called LabQuest to address students' difficulties in understanding the concept of laboratory quality management through lectures and theoretical learning.